O sistema de precedentes e a fundamentação de sentenças criminais na Justiça Federal do Maranhão - NOGUEIRA, André Márcio Costa (2022)
The present dissertation deals with the system of formally binding precedents structured from the validity of the new Civil Procedure Code. It seeks to investigate the basis of criminal decisions made by magistrates who work in the Federal Courts with criminal competence in the Judiciary Section of the State of Maranhão, based on a search in the jurisprudence database of the Federal Regional Court of the 1st Region, in order to explore the dynamics and the functionality of the techniques for applying precedents, the rejection, distinction or overcoming or the use of precedents as an argument of authority. As a problem, it discusses whether the facts and the law deduced in the selected decisions are disconnected from those that gave rise to the edition of the precedent by the Superior Courts in view of the presumption that the res judicata would not bear similarity to the ratio decidendi of the precedents. It explores, from the argumentative discourse developed by the magistrates in the decisions researched, the occurrence of hits with the determining reasons of the selected precedents or the verification of hermeneutic mismatch. The methodological approach favored a qualitative analysis of the decisions that were selected, aiming to verify, from the factual and legal aspects of each specific case, if the precedents were properly considered and identified eventual differences between the models of reasoning used in the cases studied according to precedent paradigms and with techniques imported from the common law system. To carry out the research, under the legal-dogmatic aspect, reference works by foreign and national authors on the theme of precedents were used, covering from the origin in the common law system to its importation to meet the Brazilian reality. Finally, it is conclusively stated that there is recognition of the relevance of precedents to ensure the guarantees of equality, legal certainty and the integrity of law and that in the cases analyzed the binding precedents selected as references for the research were observed.